2019
DOI: 10.1248/bpb.b18-00612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbial Metabolites of (−)-Epigallocatechin Gallate on Glucose Uptake in L6 Skeletal Muscle Cell and Glucose Tolerance in ICR Mice

Abstract: Glucose uptake ability into L6 skeletal muscle cell was examined with eleven kinds of ring fission metabolites of ()-epigallocatechin gallate (EGCG) produced by intestinal bacteria. The metabolites 5-(3,5-dihydroxyphenyl)-γ-valerolactone (EGC-M5), 4-hydroxy-5-(3,4,5-trihydroxyphenyl)valeric acid (EGC-M6), 5-(3,4,5-trihydroxyphenyl)-γ-valerolactone (EGC-M7) and 5-(3-hydroxyphenyl)valeric acid (EGC-M11) have been found to promote uptake of glucose into L6 myotubes significantly. EGC-M5, which is one of the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Modifying effects of EGCG on gut microbiota has been proposed as one of the potential mechanisms of anti-obesity activity of EGCG [ 26 ]. Moreover, recent studies have demonstrated that several microbial metabolites of EGCG generated in the gastrointestinal tract are absorbed into the systemic circulation [ 27 , 28 ] and effectively improve insulin sensitivity and glucose tolerance in rodent models [ 29 ]. Although we did not examine the levels of the metabolites in plasma or tissues, we speculated that the microbial metabolites of EGCG might contribute to the anti-obesity effects of EGCG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Modifying effects of EGCG on gut microbiota has been proposed as one of the potential mechanisms of anti-obesity activity of EGCG [ 26 ]. Moreover, recent studies have demonstrated that several microbial metabolites of EGCG generated in the gastrointestinal tract are absorbed into the systemic circulation [ 27 , 28 ] and effectively improve insulin sensitivity and glucose tolerance in rodent models [ 29 ]. Although we did not examine the levels of the metabolites in plasma or tissues, we speculated that the microbial metabolites of EGCG might contribute to the anti-obesity effects of EGCG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the large intestine, there are 11 colonic microbial ring-fission metabolites of EGC (EGC-M1–M11) (Table 1, Figure 1) as described by Takagaki et al, i.e. 1-(3,4,5-trihydroxyphenyl) 3-(2,4,6-trihydroxyphenyl)-propan-2-ol (EGC-M1), 4-dehydroxylated epigallocatechin (EGC-M2), 1-(3,5-dihydroxyphenyl)-3-(2,4,6-trihydroxyphenyl)-propan-2-ol (EGC-M3), 4-hydroxy-5-(3,5-dihydroxyphenyl) valeric acid (EGC-M4), 5-(3,5-dihydroxyphenyl)-γ-valerolactone (EGC-M5), 4-hydroxy-5-(3,4,5-trihydroxyphenyl) valeric acid (EGC-M6), 5-(3,4,5-trihydroxyphenyl)-γ-valerolactone (EGC-M7), 3-(3,5-dihydroxyphenyl) propionic acid (EGC-M8), 5-(3,5-dihydroxyphenyl) valeric acid (EGC-M9), 5-(3,4,5-trihydroxyphenyl) valeric acid (EGC-M10), and 5-(3-hydroxyphenyl) valeric acid (EGC-M11) [39,40,41]. Among them, EGC-M5 and EGC-M7 were found to be the main metabolites in mice, rat, and human plasma, urine, and bile [42].…”
Section: Bioactivity Of Egcg and Its Metabolites In The Brainmentioning
confidence: 99%
“…There was a significant decrease in SBP 2 h after administration (150 mg/kg) of EGC-M7 and 4 h after administration (200 mg/kg) of EGC-M5, compared to the control group [67]. More recently, EGCG microbial metabolites were found to have antidiabetic effects in vitro and in vivo [41]. Glucose uptake ability of EGCG metabolites was measured with differentiated rat L6 myoblast cells by using 2-deoxyglucose.…”
Section: Bioactivity Of Catechin Ring-fission Metabolitesmentioning
confidence: 99%
“…Some inhibitory compounds bind to and result in the structural alteration of α‐glucosidase (Fang et al., ; Liu, Zhang, Wei, & Lin, ). Furthermore, one flavonoid, epigallocatechin gallate, suppresses glucose uptake in skeletal muscle cells and shows glucose tolerance in mice (Takagaki et al., ); thus, catechin‐like compounds may also affect glucose uptake. Based on these results, we hypothesize that C7G and E7G inhibit α‐amylase and α‐glucosidase activity through direct binding.…”
Section: Resultsmentioning
confidence: 99%